Distractions in the Operating Room: the Prevalence of Mobile Device Uses Among Anesthesia Staff, A Cross- Sectional Study - Abdulrhman Alamri; Mohammed Alshehri; Abdulsalam Alahmari; Waleed Alharbi; Fahad Alanazi; Ahmad Adnan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Distractions are frequently present in healthcare settings and can significantly impede the performance of complex tasks that demand high levels of cognitive processing. Aim: This goal of this investigation to assess the prevalence of distractions in the operating rooms due to the use of mobile devices. Patients and methods: This was a cross- sectional investigation design included 175 participants using a self-administered validated questionnaire between April 2023 and May 2023 conducted in the three referral hospitals: King Fahad Military Medical City (KFMMC), Airbase Hospital, and Armed Forces Hospital, in Jubail, Saudi Arabia. Results: Out of the total respondents, 93.7% (n=175) reported using smartphones while providing care to anesthetized patients. The most frequent purposes for smartphone usage were making phone calls (70.3%, n=123), social media (33.7%, n=59), anesthesia App (31.4%, n=55), and surfing the internet (28.0%, n=49). However, 54.3% (n=95) of the respondents claimed that they rarely or never used their smartphones through critical stages of anesthesia. While 50.9(n=89) of the respondents reported that they were never distracted by smartphone use,53% (n=93) reported witnessing their colleagues being distracted by smartphone utilization at least once. Conclusion: Mobile devices are frequently used in for non- medical purposes in the operating room in the eastern region of Saudi Arabia. While distraction due to mobile devices use is still a concern, there is currently no evidence-based data available to determine if restrictions on mobile devices use are necessary.